Biochemical and molecular modulation of CCl4-induced peripheral and central damage by Tilia americana var. mexicana - Elvia Coballase-Urrutia; Noemí Cárdenas-Rodríguez; María Carolina González-García; Eithan Núñez-Ramírez; Esaú Floriano-Sánchez; María Eva González-Trujano; Berenice Fernández-Rojas; José Pedraza-Chaverrí; Hortencia Montesinos-Correa; Liliana Rivera-Espinosa; Aristides III Sampieri; Liliana Carmona-Aparicio (Elsevier, 2017)
Around the world, species from the genus Tilia are commonly used because of their peripheral and central medicinal effects; they are prepared as teas and used as tranquilizing, anticonvulsant, and analgesic agents. In this study, we provide evidence of the protective effects of organic and aqueous extracts (100 mg/kg, i.p.) obtained from the leaves of Tilia americana var. mexicana on CCl4-induced liver and brain damage in the rat. Protection was observed in the liver and brain (cerebellum, cortex and cerebral hemispheres) by measuring the activity of antioxidant enzymes and levels of malondialdehyde (MDA) using spectrophotometric methods. Biochemical parameters were also assessed in serum samples from the CCl4-treated rats. The T. americana var. mexicana leaf extracts provided significant protection against CCl4-induced peripheral and central damage by increasing the activity of antioxidant enzymes, diminishing lipid peroxidation, and preventing alterations in biochemical serum parameters, such as the levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), γ-globulin (γ-GLOB), serum albumin (ALB), total bilirubin (BB), creatinine (CREA) and creatine kinase (CK), relative to the control group. Additionally, we correlated gene expression with antioxidant activity in the experimental groups treated with the organic and aqueous Tilia extracts and observed a non-statistically significant positive correlation. Our results provide evidence of the underlying biomedical properties of T. americana var. mexicana that confer its neuro- and hepatoprotective effects.